3(2x – 3) + 2(x + 1) = 3x + 18
Soluções para a tarefa
Respondido por
0
olá,
Vamos lá,
3(2x-3) + 2(x+1) = 3x +18
6x - 9 + 2x + 2 = 3x +18
6x + 2x -3x = 18 +9 - 2
5 x = 25
x = 5
bons estudos!
Vamos lá,
3(2x-3) + 2(x+1) = 3x +18
6x - 9 + 2x + 2 = 3x +18
6x + 2x -3x = 18 +9 - 2
5 x = 25
x = 5
bons estudos!
Respondido por
0
3( 2x -3) + 2(x + 1 ) = 3x + 18 ∴ 6x - 9 + 2x + 2 = 3x + 18
8x -3x = 18 +9 - 2 ∴ 5x = 27 - 2 ∴ 5x = 25
x=25/5= 5
8x -3x = 18 +9 - 2 ∴ 5x = 27 - 2 ∴ 5x = 25
x=25/5= 5
Perguntas interessantes